ASEAN currency crises and contagion effects - Yusoff, Mohammed; Abdul Majid, Muhamed Zulkhibri (Curtin University, 2000)
This study examines the determinants of currency crises in ASEAN countries. The empirical results indicate that reserves inadequacy, an increase in banks' claims on the private sector, a deteriorating trade balance and misalignment of real exchange rates increase the probability of a speculative attack on a currency. The results also suggest that currency crises could be contagious.